Environmental education in China - McBeath, Gerald A.; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2014)
'The combined expertise of the McBeaths and their two associates is truly impressive: academic careers in science and politics and substantial work concerning the environment in China. This expertise is well integrated in this excellent analysis of environmental education in China. The depth of detail in the book is extraordinary for a discussion of Chinese public policy; the interpretations and conclusion are sophisticated and convincing; and there are several thoughtful policy recommendations as well.'--Cal Clark, Auburn University, US. 'Facing severe environmental deterioration for several decades, it is no surprise that China pays attention to environmental education as part of its mitigation strategies. This volume provides a useful overview of the development, state of the art and diversity of China's system of environmental education. Most interestingly, it details the similarities and differences with Western environmental education developments, both within and outside formal schools and universities.'--Arthur Mol, Wageningen University, the Netherlands. China's environmental issues have been the subject of global criticism long before authors Gerald McBeath and Jenifer Huang McBeath began their study, yet often overlooked are the sizable efforts of the Chinese people and government to change attitudes and behavior in order to improve environmental outcomes. This much-needed book offers a comprehensive introduction to environmental education in China, from consideration of the environment in Confucian philosophy and provision of environmental education in schools and colleges, to the role of non-state actors and the media. The authors' examination of conditioning factors and educational variation within China - particularly their focus on the application of directives, new guidelines and analysis of teacher training in compulsory, secondary and college education - offers an insightful measure of the efficacy of environmental education over time. This unique book will appeal to researchers, scholars and educators interested in the areas of comparative education and environmental studies, both in China and internationally.
1. Introduction to China's environmental education project -- 2. Confucianism as an environmental ethic -- 3. Environmental education in China's primary and middle schools -- 4. The environment in post-secondary education and the "Green University" in China -- 5. Environmental education in China's training of teachers -- 6. The media and environmental education -- 7. Non-state actors (NSAs) and environmental education -- 8. Environmental education variation in China -- 9. Measuring changes in environmental consciousness, knowledge and behavior -- 10. Environmental education differences in greater China -- 11. Conclusion.
Includes index.
Description based on online resource; title from title screen (viewed December 2, 2014).
Keywords: Environmental education -- China; Electronic books